The Role of Cell-Free Fetal DNA as a Preventative Attempt to Decrease the Severity of Genetic Disorders: A Review (Medico Legal Update, 2021)
The development of prenatal diagnosis has developed very rapidly over decades. Prenatal screening isapplied to a mother with high-risk pregnancy (threatening the life of the fetus), such as a too-old mother ora too-young mother and having a certain disease in her medical history. Up until now, the curative methodto treat genetic disorder is still developed and perfected. Therefore, a preventative action during pregnancyis important to do, such as Noninvasive Prenatal Testing (NIPT). NIPT method that is widely developedis the circulating cell-free fetal DNA (cffDNA) testing that can be useful for determining the fetal gender,the identification of specific single-gene disorders, blood type, paternity determination, and the potency ofregular use for testing chromosomal abnormalities. The detection of cell-free fetal DNA in the maternal bloodcirculation provides a new expectation for NIPT, especially preventing the severity of genetic disorders.